Citizenship, nationality, and migration in Europe - Cesarani, David; Fulbrook, Mary, 1951- (Routledge, 1996)
Throughout Europe longstanding ideas of what it means to be a citizen are being challenged. The sense of belonging to a nation has never been more in flux. Simultaneously, nationalistic and racist movements are gaining ground and barriers are being erected against immigration. This volume examines how concepts of citizenship have evolved in different countries and varying contexts. It explores the interconnection between ideas of the nation, modes of citizenship and the treatment of migrants. Adopting a multi-disciplinary and international approach, this collection brings together experts from several fields including political studies, history, law and sociology. By juxtaposing four European countries - Britain, France, Germany and Italy - and setting current trends against a historical background, it highlights important differences and exposes similarities in the urgent questions surrounding citizenship and the treatment of minorities in Europe today.